Analysis of the correlation between body composition, construction and aerobic capacity in teenage team sport training - Matłosz, Piotr; Michałowska, Jadwiga; Sarnik, Grzegorz; Herbert, Jarosław; Przednowek, Krzysztof; Grzywacz, Renata; Polak, Ewa (Uniwersytet Rzeszowski, 2018)
Introduction. Research results indicate that a low level of physical fitness is associated with a high percentage of fat in the body and low levels of physical activity. The aim of this work was to assess the relationships between selected morphological indicators, and the level of aerobic capacity in adolescents attending the schools with team sports. Material and methods. The studies covered students participating in sports in middle school and high school; the study group included 90 boys aged 13-19 years. Body height and weight were measured as well as waist and hip circumference. Body weight components were assessed by using a Tanita Body Composition Analyzer. A Fitnessgram® test battery was used to assess physical fitness. Results. Research results indicates systematic increase of somatic characteristics such as weight, body height and waist and hips circuits with age. Taking into account the results obtained with the PACER test indicate a very good aerobic capacity of tested boys. Conclusions. Age is a factor that improves motor fitness of physically active adolescents. There is no linear relationship between BMI and fitness among the boys who regularly train team sports, but both lower and higher BMI values seem to be connected with lower physical fitness.
Keywords: fitnessgram; adolescents; cardio respiratory fitness